IMPLEMENTASI PERATURAN DAERAH NOMOR 2 TAHUN 2013 TENTANG PENANGGULANGAN HIV-AIDS DI KABUPATEN KEBUMEN (Telaah Pasal 7) - Aulia Nugrahaeni; Aloysius Rengga (Journal of Public Policy and Management Review, 2017)
According to Local Regulation No. 2 of 2013 on HIV / AIDS Control in Kebumen District is an effort by the government to overcome HIV and AIDS disease in Kebumen Disrict. Kebumen District has a high number of cases found and has an increasing trend every year. The purpose of this study is to describe how the implementation of Local Regulation No. 2 of 2013 on HIV / AIDS Control in Kebumen District and to find out the factors driving and inhibiting Local Regulation No. 2 of 2013 on HIV / AIDS Control in Kebumen District. This research uses descriptive qualitative research method. Data collection was done by interview, observation and literature study. The informants in this study were the staff of the Kebumen District AIDS Commission, the Kebumen District Health Office staff, members of the Peer Support Group and the community. The results show that the implementation of the law has not been successful because it is ineffective in solving HIV / AIDS related problems. In this study also found the driving factors of the implementation of local regulations are resources, disposition and bureaucratic structure, while the inhibiting factors is communication. Recommendations that can be given are the selection of appropriate communication methods, conducting regular socialization activities, providing training to cadres in the field and increasing community participation.